2011
DOI: 10.1111/j.1439-0396.2009.00984.x
|View full text |Cite
|
Sign up to set email alerts
|

Digestive enzymes along digestive tract of a carnivorous fish Glyptosternum maculatum (Sisoridae, Siluriformes)

Abstract: This study attempted to determine the presence, distribution and levels of digestive proteases, pepsin, amylase and lipase in the homogenates of digestive tract of a freshwater, cold-adapted, carnivorous teleost of Tibet, Glyptosternum maculatum (n= 10, mean weight: 129.6±28.9 g, mean length: 195.1±16.6 mm, approximately 6 years old), at different temperatures and pH levels. The descending order of protease activity was as follows: stomach (pepsin, 16.16±0.96 U/mg protein), anterior intestine (3.18±0.25 U/mg p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
2
3

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 32 publications
8
40
2
3
Order By: Relevance
“…Similar data have been reported for Scleropages formosus, Solea senegalensis and Glyptosternum maculatum (Natalia, Hashim, Ali, & Chong 2004;Saénz et al 2005;Xiong, Xie, Zhang, & Liu, 2011). Pepsin is the main acid protease in fish stomach, and the first protolithic enzyme requires it for breaking large polypeptide chains (Tengjaroenkul, Smith, Caceci, & Smith, 2000;Zhao, Budge, Ghaly, Brooks, & Dave, 2011); it showed an optimal pH of 2, reported earlier for S. senegalensis, Scophthalmus maximus L. and C. carpio L. (Saénz et al 2005;Wang, Wang, Wang, Xue, & Sun, 2006;Al-Saraji, & Nasir, 2013).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar data have been reported for Scleropages formosus, Solea senegalensis and Glyptosternum maculatum (Natalia, Hashim, Ali, & Chong 2004;Saénz et al 2005;Xiong, Xie, Zhang, & Liu, 2011). Pepsin is the main acid protease in fish stomach, and the first protolithic enzyme requires it for breaking large polypeptide chains (Tengjaroenkul, Smith, Caceci, & Smith, 2000;Zhao, Budge, Ghaly, Brooks, & Dave, 2011); it showed an optimal pH of 2, reported earlier for S. senegalensis, Scophthalmus maximus L. and C. carpio L. (Saénz et al 2005;Wang, Wang, Wang, Xue, & Sun, 2006;Al-Saraji, & Nasir, 2013).…”
Section: Discussionsupporting
confidence: 73%
“…and Xiong et al (2011) reported an optimal temperature for acid proteases at 50-60°C in B. splendens and G. maculatum with denaturalizing after 60°C. Although, pepsin in C. undecimalis showed an optimal temperature at 75°C.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study were lower than previous studies on Glyptosternum maculatum (Xiong, Xie, Zhang & Liu, 2010). The incubation time differences in this study were shorter than previous research indicating one cause of the differences in the results of this research.…”
Section: Resultscontrasting
confidence: 56%
“…Aktivitas protease tertinggi dijumpai pada organ usus terutama usus bagian anterior. Pola yang sama juga dijumpai pada ikan Oreochromis niloticus (Klahan et al, 2009), Glyptosternum maculatum (Xiong et al, 2011), dan Osphronemus gouramy (Susilo et al, 2015).…”
Section: H a S I L D A N P E M B A H A S A Nunclassified
“…Penelitian sebelumnya menunjukkan bahwa aktivitas amilase terdeteksi pada beberapa organ pencernaan seperti hepatopankreas dan intestine pada sidat spesies Anguilla rostrata (Wang, 2007), dan Anguilla anguilla (Jingliang et al, 2008). Rendahnya keberadaan amilase di sepanjang saluran pencernaan juga dijumpai pada Glyptosternum maculatum (Xiong et al, 2011). Hal ini mengindikasikan bahwa hepatopankreas pada ikan karnivora mensekresi amilase kedalam usus dalam konsentrasi yang rendah.…”
Section: H a S I L D A N P E M B A H A S A Nunclassified